Attitude, readiness and utilisation of artificial intelligence: a cross-sectional study among undergraduate medical students in a medical college, Kolkata - Pattanayak, Shalini; Gupta, Kalpana; Ray, Kuntala; Saha, Subhosri; Basu, Mausumi (International Journal Of Community Medicine And Public Health, 2025)
Background: Artificial intelligence (AI) is used to analyze various digital information and ease the diagnosis and adapted therapies. This study was conducted to assess the attitude and readiness towards AI among undergraduate medical students and to find out their utilization. Methods: An online survey was performed among 443 medical students with a pre-tested pre-validated questionnaire, Sit’s attitude scale and MAIRS-MS scale in 5 point Likert scale. The attitude was categorized as ‘favourable’ and ‘unfavourable’ based on the median of the overall attitude score. Scores for each of the four sub-domains under the readiness scale of MAIRS-MS were calculated, and an overall mean±SD score was obtained by summing up the mean scores. ANOVA tests were done to determine group differences, and Spearman’s correlation coefficients was calculated to examine associations between individual variables. Results: Almost all participants were aware of the use of AI in health care. Almost 56% had a ‘favourable attitude’ towards AI. 41.08% agreed to use AI applications for its purpose, and 32.27% agreed to use AI technologies effectively. The overall mean and SD score of readiness toward AI was 66.13±17.45. Spearman’s correlation revealed a moderately positive correlation between the overall readiness score and attitude score (Spearman’s rho- 0.483, p<0.001). 292 (66.0%) of the total participants use an AI-based application, out of which 85.0% of them commonly use Chat GPT. Conclusions: Nearly half of the study participants showed a favorable attitude toward the role of AI in healthcare. They had a noticeable readiness to incorporate AI in medical education.